A Theological Dialogue on The Notion of Conscience (Vicdân) in Christianity and Turkish Islamic Thought - Idris Danisman (Jurnal Dialog, 2023)
The recent human crises in the world caused by believers of the same religions fighting amongst themselves— such as Muslims in the Middle East and Christians in the recent Russo-Ukrainian War—have once again raised the question of the function of individual conscience (the ability to distinguish bad from good) in society. How can individuals judge what is good or bad when religious communities of same faith confuse the judgment of the religion’s followers by accusing others of wrongdoing while proclaiming themselves to be right? Would a conscience enable individuals to assess the moral quality of their thoughts, words, and deeds without being affected by society? This paper attempts to answer these questions by conducting a comparative analysis of the concept of vicdân (conscience)—the Turkish and Persian equivalent of the English word “conscience”—in Christianity and Turkish Islamic thought, and concludes that, although every individual is endowed with a conscience as a potential faculty, it must be discovered and cultivated by the individual through intellectual effort and represented in the society (collective conscience) in order to function as a righteous judge distinguishing good from bad and right from wrong in difficult times.